Determination of optimum parameters in the implementation of an antnet routing algorithm for improving data transmission - Cruz de la Cruz, Jose Emmanuel (2016)
The main objective on this research is the development of finding the optimal parameters for a routing algorithm for network routers based on the ant algorithm described as AntNet. The optimum parameters for this type of algorithm improve a more efficient alternative to those given by the RIP, EIGRP and OSPF routing protocols, to be applied in a data network. This shall be tested in two networks and routers defined, taking the same characteristics for the three groups: RIP, OSPF and by the result provided by the genetic algorithm implemented using a static network. The system recognizes the best path between networks of routers, based on the principle of AntNet networks or networks of ants, which are the best way from exploring almost all roads, using estimergia to go there and make optimal. MatLab was used to detect the best way. Later this road was implemented in a real network data, sending a test file in compressed format. Its efficiency compared with RIP and OSPF protocols are checked. For validation of the network, compressed files, which were sent for ten consecutive times and the results were taken using a server and a network connected by the given client used. The server and client are implemented in Linux, to measure the arrival time of the file and thus the data transfer rate. It was found that the routing algorithm, under the optimal parameters found, provided a reliable alternative for routing data networks.